Septic arthritis of the temporomandibular joint–a case report and review of the literature - Araidy, Shareef; Maalouf, Naseem; Front, Eran; Abu El-Naaj, Imad (Frontiers in Oral Health, 2025)
Septic arthritis occurring in the temporomandibular joint (TMJ) has received significantly less attention than it deserves. This condition can severely compromise joint functionality, especially if left untreated. Its typical presentation includes pain, fever, swelling, and the loss of TMJ functions. We report a case of TMJ septic arthritis arising in the left joint of a 52-year-old woman. Our report, along with a review of the literature, highlights the importance for early detection of TMJ septic arthritis, its clinical and radiographic characteristics, as well as the management of this rare disease and the proposed etiologies of its pathogenesis. Raising awareness among healthcare providers can promote early diagnosis, improving outcomes and preventing complications of TMJ septic arthritis.